Polityczność sztuki. Analiza pracy Zbigniewa Libery pt. LEGO. Obóz koncentracyjny z 1996 roku - Lorenc, Magdalena (Wydawnictwo Naukowe WNPiD UAM, 2012)
The objective of the paper is to analyze Zbigniew Libera’s Lego. Concentration Camp from 1996, which is considered to be one of the most important Polish works of art in the 1990s. Lego exemplifies the problem of the politicality of art which consists of art’s involvement in politics. The considerations on the permeation of the fields of politics and esthetics constitute a sig- nificant part of the work of French philosopher Jacques Ranciere, whose concepts provide the theoretical foundations for the analysis of Libera’s Lego. The juxtaposition of toys with the symbol of the Holocaust raises questions about the role of art in uncovering the discourse of power as understood by Michel Foucault, the influence of public policies (cultural, educational policies and the policy towards the past) on art and the borders of commercialization and trivialization of the symbols of collective memory. Libera’s Lego is a transgressive work, representing the trend of so-called critical art in modern Polish art. The artist used artistic methods to break the cultural taboo that concerns the presentation of the non-presentable. Libera showed the past and the present, the former by re- ferring to the topic of the Holocaust, indicating the pragmatism of the Nazi system, and the lat- ter by uncovering the laws of the teaching process, carried out by means of repeating patterns. Above all, however, Libera showed that artistic activity can be a form of expressing interests and can influence the shape of public policies.
An Analysis of Zbigniew Libera’s Lego. Concentration Camp from 1996
Keywords: sztuka; polityczność; Zbigniew Libera; Holocaust